Проблеми становлення та розвитку біржового ринку України - Завадських, Ганна Миколаївна; Завадских, Анна Николаевна; Zavadskykh, Hanna (Мелітополь: ТДАТУ, 2018)
UK: Розглянуто проблеми і перешкоди в розвитку біржової торгівлі в Україні. Визначено перспективи його подальшого розвитку.У статті розглянуто проблеми біржової торгівлі в Україні в умовах нестабільної економіки. Проаналізовано основні тенденції та закономірності розвитку вітчизняних товарних бірж. Наведено основні характерні особливості функціонування вітчизняних товарних бірж та фактори впливу на процес становлення біржового товарного ринку в Україні EN: The current legislative framework, which regulates stock exchange activity and the stock market of Ukraine, is in place in the absence of specialized national normative acts. The stock market of Ukraine is artificially created and does not fulfill its functions. Exchanges mainly work in their isolated business environment or are created to secure business interests of a certain group of people. An important relative indicator that characterizes the effectiveness of stock trading is the indicator of the liquidity of exchange trades. Due to the wide variety of financial instruments in Ukraine there is only a limited range of them with a limited set of characteristics of profitability, riskiness, security, etc. A limited number of investment companies and brokers, analytical and consulting companies impede the formation of the labor market of stock market professionals. The Ukrainian stock market is significantly behind the scale of the agreements, the level of trade software. Ukrainian enterprises in general and the subjects of exchange institutions, in particular, are characterized by a low level of compliance with the rules and ethical norms of doing business.
Problems of formation and development of Ukraine’s exchange market
Keywords: біржовий ринок; біржа; біржова діяльність; біржова торгівля; товарна біржа; біржова угода; біржовий товар; ліквідність; біржові торги; волатильність ринку; фінансові інструменти; stock market; stock exchange; stock exchange; stock exchange; commodity exchange; stock exchange agreement; stock commodity; liquidity; stock trading; volatility of the market; financial instruments